2021
DOI: 10.1002/etc.4964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Size on Methylmercury Concentrations in Shoreline Spiders: Implications for Their Use as Sentinels

Abstract: Shoreline spiders have been proposed as sentinels to monitor aquatic contaminants including methylmercury (MeHg). The present study examined the effect of spider body size on MeHg concentrations in shoreline spiders. We collected 6 taxa of spiders belonging to 4 families (orb-weavers [Araneidae], long-jawed orb weavers [Tetragnathidae: Tetragnatha sp.], jumping spiders [Salticidae], and wolf spiders [Lycosidae: Pardosa sp., Rabidosa sp., and Schizocosa sp.]) from the shorelines of 14 human-made ponds at the Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The effect of riparian spider age/size has only been examined for metals. Negative correlations between Hg and size (Pennuto & Smith, 2015) and Cd and size/age class (Ramirez et al, 2011) have been reported, whereas positive correlations were reported between Hg and size in four riparian spider taxa (Hannappel et al, 2021). Hannappel et al (2021) reported a lack of correlation between Hg and size in two riparian spider taxa, whereas Ramirez et al (2011) reported a lack of correlation between size and Zn, Cu, and Cr in riparian spider tissues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of riparian spider age/size has only been examined for metals. Negative correlations between Hg and size (Pennuto & Smith, 2015) and Cd and size/age class (Ramirez et al, 2011) have been reported, whereas positive correlations were reported between Hg and size in four riparian spider taxa (Hannappel et al, 2021). Hannappel et al (2021) reported a lack of correlation between Hg and size in two riparian spider taxa, whereas Ramirez et al (2011) reported a lack of correlation between size and Zn, Cu, and Cr in riparian spider tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Negative correlations between Hg and size (Pennuto & Smith, 2015) and Cd and size/age class (Ramirez et al, 2011) have been reported, whereas positive correlations were reported between Hg and size in four riparian spider taxa (Hannappel et al, 2021). Hannappel et al (2021) reported a lack of correlation between Hg and size in two riparian spider taxa, whereas Ramirez et al (2011) reported a lack of correlation between size and Zn, Cu, and Cr in riparian spider tissues. Although age‐related bioaccumulation occurs in other sentinels (e.g., fish; Wiener et al, 2003), its importance in riparian spiders has not been well established.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the distance that mud daubers forage from their nests is unknown, and until this is resolved, using spiders from mud dauber nests to identify highly localized areas of contamination could be problematic. In addition, mud daubers may prefer smaller spiders (Coville 1987), which have relatively low levels of Hg contamination (Hannappel et al 2021), and mud daubers are known to be selective foragers (e.g., Rau 1935; Muma and Jeffers 1945). For example, although we have observed large populations of Tetragnathidae along the Trinity River, in the present study we found few Tetragnathid spiders in mud dauber nests.…”
Section: Resultsmentioning
confidence: 99%